Strategi Menulis Abstrak Berbahasa Inggris - Khudriyah Khudriyah (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
Abstraction is an important thing in a scientific work, by reading it you can find out what things are in the content of a scientific paper. However, creating abstractions is not easy. The aim of this counseling is to make it easier for STIT al Urwatul Wutsqo Jombang students to be able to understand how to translate abstracts into English through the demonstration method. The results of the study showed that there was a significant comparison between the means before and after providing mentoring where the mean was found (43.89, increased to 68.61) and the results of t count > t table (14, 632 > 2.1098) so it was concluded that this mentoring was successful .